2021
DOI: 10.2147/opth.s301439
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors Associated with Retinopathy of Prematurity in Peru

Abstract: The purpose of this research is to determine retinopathy of prematurity (ROP) prevalence and possible risk factors associated with ROP development in newborns admitted to a neonatal unit of a Peruvian National Reference Hospital. Patients and Methods: This retrospective study included 216 preterm infants. The data were collected between January 2016 and December 2018. All infants were examined according to Peruvian guidelines for screening and treatment of ROP. The association of clinical risk factors and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The univariate logistic regression models of our study indicated that BW, GA, Apgar1, Apgre5, delivery room intubation and positive pressure ventilation, delivery room chest compressions and/or resuscitation medications, surfactant, pneumothorax, intubation within 24 hours of life, intubation any time during the NICU stay, any pRBC transfusion during the NICU stay, and peak bilirubin were all risk factors for ROP development. Our data also showed that premature infants with ROP had signi cantly lower GA and BW and lower Apgar1 and Apgar5 than non-ROP infants, which was consistent with the ndings of previous studies (12).…”
Section: Discussionsupporting
confidence: 93%
“…The univariate logistic regression models of our study indicated that BW, GA, Apgar1, Apgre5, delivery room intubation and positive pressure ventilation, delivery room chest compressions and/or resuscitation medications, surfactant, pneumothorax, intubation within 24 hours of life, intubation any time during the NICU stay, any pRBC transfusion during the NICU stay, and peak bilirubin were all risk factors for ROP development. Our data also showed that premature infants with ROP had signi cantly lower GA and BW and lower Apgar1 and Apgar5 than non-ROP infants, which was consistent with the ndings of previous studies (12).…”
Section: Discussionsupporting
confidence: 93%
“…Obviously, the relationship between vaginal delivery and threshold ROP may be a link, although not necessarily a causal relationship [27] . During the natural delivery process, the mechanism of vaginal delivery and the stress dynamics may be harmful to the fetal cerebral blood vessels, leading to ischemia and subsequent reperfusion and/or oxidative stress, accompanied by related imbalance of hyperoxiahypoxia [28] .…”
Section: Resultsmentioning
confidence: 99%
“…A multicenter study (CRYO-ROP) that enrolled 4,099 preterm infants with birth weights of less than 1251g showed that lower birth weight and lower gestational age significantly contributed to the development of retinopathy in preterm infants [6]. The thesis has been corroborated by the results of numerous metaanalyses reported in scientific studies [7][8][9].…”
Section: Fetal Age and Birth Weightmentioning
confidence: 96%